2016
DOI: 10.1002/pbc.26258
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of safety and efficacy of cytotoxic versus molecularly targeted drugs in pediatric phase I solid tumor oncology trials

Abstract: In phase I pediatric solid tumor trials, ORRs were significantly higher for cytotoxic versus targeted agents. SDRs were similar in targeted and cytotoxic drug trials. Patients treated with cytotoxic agents were more likely to experience hematologic G3/4 toxicities than those patients receiving targeted drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 147 publications
(176 reference statements)
0
3
0
Order By: Relevance
“…A review of the literature suggests that in addition to its possibilities as a curative agent, targeted therapies can be less toxic than their cytotoxic counterparts. Two recent meta-analyses of phase I pediatric clinical trials showed that dose-limiting toxicity was found to be higher in cytotoxic therapies than in targeted drugs 19,20. Though our study was not designed to compare outcome or survival, we observed the application of targeted therapeutics among 12 patients and followed their outcome along with toxicities, if any.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature suggests that in addition to its possibilities as a curative agent, targeted therapies can be less toxic than their cytotoxic counterparts. Two recent meta-analyses of phase I pediatric clinical trials showed that dose-limiting toxicity was found to be higher in cytotoxic therapies than in targeted drugs 19,20. Though our study was not designed to compare outcome or survival, we observed the application of targeted therapeutics among 12 patients and followed their outcome along with toxicities, if any.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent meta-analyses of phase I pediatric clinical trials showed that dose-limiting toxicity was found to be higher in cytotoxic therapies than in targeted drugs. 19,20 Though our study was not designed to compare outcome or survival, we observed the application of targeted therapeutics among 12 patients and followed their outcome along with toxicities, if any. We noted that of our 12 patients who received targeted therapy, 2 patients experienced drug-related adverse effects leading to discontinuation of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…From each study, we extracted data related to: study characteristics (e.g., year of results publication, phase, funding, study status), patient characteristics (e.g., age, number of adverse events (AEs) and response rates of anticancer agents in phase I adults as well as pediatric clinical trials [16][17][18][19][20]; others focused on the risks and benefits of particular drugs [21,22] or interventions in specific cancer types [23,24]. Historically, targeted drugs are considered to have a better toxicity profile than chemotherapy agents [25,26].…”
Section: Data Extractionmentioning
confidence: 99%